Hospital admissions and the financial cost incurred by the elderly patients at a tertiary care centre in Gokarneshwor Municipality, Kathmandu, Nepal - Shrestha, Niraj; Paudel, Leepy; Baral, Prakriti (Nepal Medical College Journal, 2023)
Population ageing is a global phenomenon and proportion of elderly people is also increasing in Nepal. However, the increased burden of chronic disease as a result of population ageing, along with medical cost incurred during hospital stay is yet to be explored in Nepal. With the aim of studying these, data of 527 patients 70 years of age and above admitted to Nepal Medical College Teaching hospital, the largest tertiary care center in Gokarneshwor Municipality, was collected from November 2021 to November 2022 and analyzed. Seventy-four percent of the patients were of 70-80 years of age and male: female ratio was almost equal to 1:1. The most common cause of admission was respiratory problems. The cost was not more than Nepali rupees 19,200 for 82% of the patients and the duration of stay was less than 6 days for 75% of the patients. No significant association was found between duration of hospital stay and the age group or the gender. Similarly, no significant association was found between the medical cost incurred during hospital stay and the age group. However, association was found between the hospital cost and gender with males more likely to have higher cost.